Comparison of Microbiota in Threatened Preterm Labor and Normal Pregnancy at RSUP DR.M. Djamil Padang - Ryfki SA, Muhammad; Yanti, Roza Sri; Utama, Bobby Indra (Andalas Obstetrics And Gynecology Journal, 2024)
One of the threats in pregnancy is threatened preterm labor. Several studies show that the composition of the microbiota in the vagina of premature births and normal pregnancies is different. This study aims to determine the comparison of microbiota in pregnancies with premature parturition and normal pregnancies at Dr M Djamil General Hospital, Padang. This research is an analytical observational study with a case–control study design conducted at the Department/SMF of Obstetrics and Gynecology, RSUP Dr. M. Djamil Padang from July – September 2023. The study population in this research were all pregnant women with a gestational age of 20-37 weeks who were diagnosed with imminens preterm labor and normal pregnant women with a gestational age of 20-37 weeks who received antenatal care at RSUP Dr. M. Djamil Padang. Respondents had vaginal swabs taken for microbiological culture at the Biomedical Laboratory, Andalas University, Padang. There were 33 respondents each in the imminence premature birth and normal pregnancy groups. Vaginal swab results showed that the most common microorganism found in normal pregnancy was Lactobacilus sp. (73%) while in threatened preterm labor Staphylococcus aureus (37%), Staphylococcus epidermidis (27%) and E.coli (15%) were more commonly found with only a small proportion of Lactobacilus sp (12%). Chi square analysis showed a significant difference between the vaginal microbiota of normal pregnant women and pregnant women with PPI. The conclusion of this study is that there is an increase in Staphylococcus aureus, Staphylococcus epidermidis and E.coli in pregnant women on PPI with a decrease in the number of normal flora, namely Lactobacilus spp.